A Filtered Past: Interpreting Salt Production and Trade Models from Two Remnant Brine-Enrichment Mounds at the Ancient Maya Paynes Creek Salt Works, Belize. (2nd January 2019) - Watson, Rachel; McKillop, Heather
ABSTRACT: The mounds at Witz Naab and Killer Bee are the only known remaining aboveground evidence of a once-thriving salt industry in Punta Ycacos Lagoon, a large saltwater system in Paynes Creek National Park, Belize. Over one hundred ancient Maya salt works dated to the Classic period (a.d. 300–900) have been submerged by sea-level rise in the lagoon. We have hypothesized that mounds were once numerous features on the landscape prior to a sea-level rise that occurred in the area during the Terminal Classic period. Lacking at these underwater sites are earthen mounds formed by discarded soil from the leaching process in which the salinity of seawater was enriched by leaching brine through salty soil. Enriching the salinity of seawater by leaching or by solar evaporation is virtually universal in ethnographic case studies. Data from the excavations are evaluated to interpret the ancient activities that produced the earthen mounds, scales of production, and how the coastal Maya of southern Belize participated in the larger Classic Maya economy.